Does social trust affect international contracting? Evidence from foreign bond covenants - Brockman, Paul; El Ghoul, Sadok; Guedhami, Omrane; Zheng, Ying (Journal of International Business Studies, 2022)
Building on rational choice institutionalism theory and Williamson’s (J Econ Lit 38(3): 595–613, 2000) four-level social analysis framework, we investigate the influence of the informal institution of social trust on debt contract design in an international setting. Using a sample of non-U.S. firms that issue bonds in the U.S. debt market, we find that Yankee bond creditors impose fewer covenants on bond issuers domiciled in countries with a high degree of social trust. We further show that the inverse relationship between debt covenants and the informal institution of social trust is more pronounced for firms from countries with weak formal institutions, as well as for firms with poor corporate governance and greater information opacity. These findings are robust to endogeneity tests, within-country analysis, various empirical models and measures of trust, and alternative hypotheses. We also show that, while a lower level of informal social trust is associated with higher borrowing costs, this relationship weakens when formal covenants are added to the debt contract (i.e., a substitution effect). Our paper contributes to the international business literature by providing new insights into the role of informal institutions (social trust) in cross-border debt contracting.